Parametric Analysis and Comparison of Ejector Expansion Refrigeration Cycles With Constant Area and Constant Pressure Ejectors - SEÇKİN, CANDENİZ (ASME, 2017)
In this work, parametric analysis of ejector expansion refrigeration cycles (EERC) with two different types of ejectors (constant area (CA) ejector and constant pressure (CP) ejector) is performed, and comparison of the results is presented. Effects of variation in operational parameters (condenser temperature, evaporator temperature, and cooling capacity) on coefficient of performance (COP), entrainment ratio (w), and pressure lift factor (P-lf) are investigated. The range of variation for evaporator temperature, condenser temperature, and cooling capacity are -5 to 15 degrees C, 50-70 degrees C, and 10-80 kW, respectively. The ejector refrigeration cycle is simulated by EES software. The obtained results are validated by the experimental data available in the literature. The refrigerant R134a is selected based on the merit of its environmental and performance characteristics. The results show that the effect of evaporator temperature is much higher than that of condenser temperature on Plf. In contrast, the influence of condenser temperature on COP is much stronger than that of evaporator temperature. It is seen that COP and Plf of ejector expansion refrigeration cycle with constant pressure ejector (CP-EERC) are higher than those of refrigeration cycle with constant area ejector.
Keywords: ejector expansion refrigeration system; two-phase flow ejector; constant area ejector; constant pressure ejector; 2-PHASE EJECTOR; PERFORMANCE-CHARACTERISTICS; R134A; MODEL